Fearful - Roberts, Lauren, 2002- (Roberts, Lauren, 2002- Powerless trilogy, 2025)
"Set during Fearless, the conclusion of the Powerless Trilogy, a mysterious figure emerges in the kingdom to both observe key characters and guide the King of Ilya"--